2016
DOI: 10.1159/000444689
|View full text |Cite
|
Sign up to set email alerts
|

Portuguese Adaptation of a Faux Pas Test and a Theory of Mind Picture Stories Task

Abstract: Background: Developmental concepts of ‘Theory of Mind' (ToM) suggest that this cognitive domain is an innate human capacity requiring input from the social environment to mature. Research suggests substantial individual differences in ToM, depending on childhood experiences, genetics, and the presence or absence of a neuropsychiatric disorder. None of the existing ToM tests for adult populations have been made available in Portuguese. Accordingly, the main objective of this study was to evaluate the psychometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 42 publications
(56 reference statements)
0
9
0
11
Order By: Relevance
“…ToM was assessed using an adult version of The faux pas test adapted from Baron-Cohen et al [1999] and Stone et al [1998]. The task was selected due to its psychometric properties [Faísca et al, 2016;Fernández-Modamio et al, 2018;Hayward & Homer, 2017;Smogorzewska, Szumski, & Grygiel, 2018;Söderstrand & Almkvist, 2012;Zalla et al, 2009]. Although the psychometric properties of the faux pas test have not been formally assessed in adolescents, it has been shown to be able to discriminate between children and adults with HFA from controls [Baron-Cohen et al, 1999;Zalla et al, 2009].…”
Section: Measures and Proceduresmentioning
confidence: 99%
“…ToM was assessed using an adult version of The faux pas test adapted from Baron-Cohen et al [1999] and Stone et al [1998]. The task was selected due to its psychometric properties [Faísca et al, 2016;Fernández-Modamio et al, 2018;Hayward & Homer, 2017;Smogorzewska, Szumski, & Grygiel, 2018;Söderstrand & Almkvist, 2012;Zalla et al, 2009]. Although the psychometric properties of the faux pas test have not been formally assessed in adolescents, it has been shown to be able to discriminate between children and adults with HFA from controls [Baron-Cohen et al, 1999;Zalla et al, 2009].…”
Section: Measures and Proceduresmentioning
confidence: 99%
“…However, another possible reason for non-significant differences of ToM scores should be considered such as a ceiling effect. Although the ToM task in our study has been widely used in nonclinical groups (Faísca et al, 2016 ; Jeon et al, 2013 ; Lee et al, 2014 ), the average score of ToMq showing near maximum score suggested the possibility of ceiling effect. However, the additional sensitivity analysis for moderation model was consistent with the significant interaction effect of ToM and CT.…”
Section: Discussionmentioning
confidence: 70%
“…Also, the Brazilian versions of the Protocole Montréal d`Évaluation de la Communication and the Faux Pas and Teste de Coerência e Inferência Local were administered to all participants to assess language development and social cognition features. 33 - 35 …”
Section: Methodsmentioning
confidence: 99%